Depicting Mu'aviah's Character in Imam Ali's Discourse - Hassan Bashir; Mahammad Janipur (Religion & Communication, 2010)
The scope of study on the history of Islam in general and Imam Ali's rule in particular has typically been restricted to a description of events, a fact which has resulted in neglecting most of the social and cultural dimensions occurred during that period of time. What can now be done to initiate a better understanding of those events is the explanation for Imam's outlook and theoretical principles through his discourse, since language proclaims the man; and by analyzing a person's words one can reach a comprehensive view of his ideas. Also, by considering the overall logic behind the available sayings of Imam and their analysis, it is possible to reconstruct a whole corpus of Imam's thought. This article seeks to make a survey of the content of Imam Ali's exchanged letters with Mu'aviah in the course of Imam's short rule, for the purpose of achieving a comprehensive view of Mu'aviah's political, intellectual, ideological and ethical principles.